Adoption of extended UTAUT model on e-learning in UAE higher education institutions - Alblooshi, Saeed Abdullatif (2021)
The fast development of e-learning technology has become a crucial aspect of learning in higher institutions of learning. Just as with any other technology, important factors affect users’ behavioural intention to adopt e-learning. Previous studies have explained the factors affecting e-learning adoption using the UTAUT model in western contexts. However, such factors or antecedents of e-learning adoption may be varied in non-western contexts. The propositions of the UTAUT model have been severally tested in the western and developed nations context, but there exist inadequate empirical validations of the propositions of the model in non-western, i.e. in developing nations. Therefore, building on already established antecedents and factors, the study sought to investigate the direct effect of the four determinants of e-learning adoption, including the added variable-service quality on HEI students’ behavioural intention to use e-learning technologies in the UAE. Furthermore, the study also examined the mediating role of perceived satisfaction, behavioural intention and perceived usefulness in the relationship between the five determinants of e-leaning adoption and the actual use of e-learning systems. Using a quantitative approach and a survey research design, data were obtained from a sample of 453 students selected from pioneering universities with e-learning infrastructures in the UAE. Data were analyzed using the partial least squares structural equation modelling (PLS-SEM). The results show that from a total of 16 direct hypotheses, only four hypotheses were rejected. Regarding the mediating analysis, the results show that perceived usefulness and perceived satisfaction significantly mediates the relationship between performance expectancy, effort expectancy, social influence, service quality, facilitating condition and the actual use of e-learning. However, students’ behavioural intention only mediates the relationship between facilitating condition and actual use of e-learning; nonetheless not mediating the relationship between performance expectancy, effort expectancy, social influence, service quality, and e-learning usage. Interestingly, the study showed that service quality plays a crucial role in HEI students’ perceived usefulness and perceived satisfaction regarding using e-learning technologies. This finding shows a novel contribution of the study in introducing a new antecedent of e-learning adoption, i.e. service quality, perceived usefulness and perceived satisfaction to the technology acceptance models in a higher education context. Consequently, future studies can explore service quality as an integral part of the antecedents of e-learning adoption in higher education in a context not covered by the scope of this study. Recommendations to relevant stakeholders in the higher education sectors were proposed.